THE TECHNOLOGY OF CULTIVATING SWEET BELL PEPPERS UNDER THE SOIL AND CLIMATIC CONDITIONS OF BUKHARA - Mukhayo Bafoevna Tagayeva; Azizova Nodira; Islomova Mushtaribegim Ramazonovna (Modern American Journals, 2025)
The article presents information on the study of methods for cultivating sweet bell pepper (Capsicum annuum L.) under greenhouse conditions in the Bukhara region, focusing on the impact of TERIA-S and Green microbiological preparations on plant growth, prevention of stress conditions, and increasing productivity.
Keywords: Sweet Bell Pepper (Capsicum annuum L.), TERIA-S and Green microbiological preparations